2022
DOI: 10.3390/curroncol29120752
|View full text |Cite
|
Sign up to set email alerts
|

A Portrait of Cord Blood Units Distributed for Transplantation from Canadian Blood Services’ Cord Blood Bank: First Analysis

Abstract: Background: The Canadian Blood Services Cord Blood Bank (CBS CBB) was created to improve access to stem cell products for transplantation for patients across ethnic groups. An analysis of distributed units is needed to assess the effectiveness of the bank to meet the needs of patients from different ethnic groups. Methods: A descriptive analysis was performed on all cord blood units distributed from the CBS’ CBB as of 30 June 2022. Results: Distribution of the first 60 units based on CBS’ CBB inventory has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To supplement the CBS SCR, the CBS' CBB was established to improve access for patients of diverse ancestry. Initial analysis of the CBS CBB's usage demonstrated that 18% of distributed cord blood units were of multi-ethnic background [48]. However, 54% of distributed cord blood units were from donors self-reporting as white, which underscores the ongoing need to collect units from this group to meet patient needs and avoid an overall reduction in total matches.…”
Section: Discussion: How Can Registries Reflect the Changing Needs? A...mentioning
confidence: 99%
“…To supplement the CBS SCR, the CBS' CBB was established to improve access for patients of diverse ancestry. Initial analysis of the CBS CBB's usage demonstrated that 18% of distributed cord blood units were of multi-ethnic background [48]. However, 54% of distributed cord blood units were from donors self-reporting as white, which underscores the ongoing need to collect units from this group to meet patient needs and avoid an overall reduction in total matches.…”
Section: Discussion: How Can Registries Reflect the Changing Needs? A...mentioning
confidence: 99%
“…Moreover, increasing numbers of registrants and patients self-report associations with more than one ethnic group, or multi-ethnicity. In recent analyses of the cord blood bank inventory at Canadian Blood Services, 18,19 we identified many combinations of ethnic groups within the multi-ethnicity category, including some who identified with Caucasian and another ethnicity as the most common subgroup. An analysis of multi-ethnic simulated recruits would be worthwhile, particularly in a country such as Canada with an evolving and growing population of people who may self-identify as multi-ethnic.…”
Section: Discussionmentioning
confidence: 99%